Najstarsze greckie inskrypcje biesiadne a początki greckiego alfabetu - Węcowski, Marek (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
As far as the early epigraphic material is concerned, the joy of the Methone excavations is that they have brought to light so much new material, but at the same time they seem to confirm many earlier scholarly insights and interpretations. Among other things, the new finds confirm the importance of convivial inscriptions at the earliest attested stage of Greek alphabetization. It is time, then, to ask some general questions about the manner in which such texts were apparently used at symposia. In particular, I focus on the fact that so many examples of earliest Greek vase-inscriptions are first-person utterances ranging from short ownership statements to elaborate poetic compositions. I try to show that to account for the relative frequency of the first-person early vase-inscriptions, we need to visualize the sympotic workings of such utterances but also conceivable sympotic functions of the vessels they adorn. Accordingly, we ought to distinguish between different shapes of vases in order to interpret their inscriptions in a sympotic context. I hope that the results of this inquiry will make it possible for us to shed a new light on the rather early phases of the use of the Greek alphabet and about the mechanisms of its spread among the Greeks at so early a date.
Keywords: sympozjon; arystokracja; arystokratyczny styl życia; biesiada grecka; inskrypcje biesiadne; poczatki alfabetu greckiego; hetery; kurtyzany greckie; rozrywki biesiadne